Financing risk and debt financing modes of Islamic bank in Malaysia: A theoretical perspective - Hidthiir, Mohamad Helmi; Bakar, Normizan (2015)
The purpose of this paper is to discuss the financing risk in Islamic banks and to explain it from the theoretical perspectives why Islamic banks concentrate on debt based financing modes. From this stance, this study focuses on the issue on how the debt financing mode could trigger financing risk.Specifically, there are two questions regarding on this issue.First, what is the nature of Islamic debt financing modes that could trigger Islamic Bank financing risk? Second, what are the important variables used by Islamic banks to monitor their financing risk? To answer these questions, this paper attempt to explain this issue utilizing agency theory, financial inter mediation theory and portfolio theory in the context of Islamic banking model.Based on these theories, this study find that the endogenous factors such as the level of capital, the management cost and efficiency and the level of asset play an important role in the financing risk management of Islamic banks and highlight the reason why Islamic Bank prefer debt-financing modes.